Case Report: A Malignant Liver and Thoracic Solitary Fibrous Tumor: A 10-Year Journey From the Brain to the Liver and the Spine - Mao, Min; Zhou, Lei; Huang, Chaojun; Yan, Xudong; Hu, Shuo; Yin, Huabin; Zhao, Qinghua; Song, Dianwen (Frontiers in Surgery, 2020)
Solitary fibrous tumors are rare neoplasms that originate from mesenchymal tissues and have been found to occur in any site, including the spine and liver. Although most of solitary fibrous tumors have benign features, only 10–20% are malignant and prone to metastasis. No previous reports have described the malignant and metastatic Solitary fibrous tumor arising in both of the liver and thoracic vertebrae. In this article, we present the case of a 60-year-old woman who underwent gross total resection of a meningeal tumor in 2007. She presented 10 years later with a thoracic vertebral mass that caused relentless pain and a lesion in the right lobe of liver. She underwent marginal excision of the T3 tumor with T2-4 pedicular screw fixation in March 2017, then right hemi-hepatectomy was performed to remove the liver lesion in June 2017. Both of the lesions were confirmed to be a metastatic and malignant tumor after surgery. The literature lacks randomized controlled trials and large studies that define the natural history of malignant solitary fibrous tumors and recommendations of precise management plan for the disease. However, the best choice for treatment is gross total resection, which probably provide the optimal treatment to achieve long-term disease-free survival.